Entrepreneurial Career Paths: Occupational Environments and the Propensity to Become Self-Employed - Alina Sorgner; Michael Fritsch (Small Business Economics, 2018)
We investigate the relationship between characteristics of an occupation-specific environment and the decision of employees to start an own business. A relatively high occupation-specific unemployment risk and high earnings risk are conducive to opt for self-employment. Also, occupations that are characterized by high self-employment rates foster entrepreneurial choice among their employees. The results suggest that career choices of future entrepreneurs are driven by different motivations than those of non-entrepreneurs. In particular, the expectation of a pronounced financial gain is critical for future entrepreneurs when they make their initial occupational choices in paid employment and it is also relevant for a self-employment choice. We also find that when future entrepreneurs enter the labor market they are more likely to choose occupations that require a relatively high variety of skills. Moreover, such occupations may promote entrepreneurship among their employees.
Keywords: L26; J24; D01; 330; entrepreneurial choice; occupation-specific determinants of entrepreneurship; unemployment risk; earnings risk; skill variety